On Harmonic Univalent Functions Defined by Dziok-Srivastava Operator - Mays S. Abdul Ameer; Abdul Rahman S. Juma; Raheam A. Al-Saphory (Tikrit Journal of Pure Science, 2022)
The purpose of this work is to present a class of harmonic univalent functions deﬁned by the Dziok-Srivastava operator. Some geometric properties like coefficients conditions, distortion theorem, convolution (Hadamard product), convex combination and extreme points are investigated.